Fantasy, film song, and 'non-resident media': Dil Se's afterlife. (4th May 2022) - Trivedi, Pragya
ABSTRACT: Mani Ratnam's Dil Se (1998), 22 years after its release and its subsequent flop in the Indian box office, was included in Hollywood Insider's 'Master of Cinema Archive' in 2020. Its songs appeared in surprising places, including Spike Lee's Inside Man (2006), and in 2020, Canadian music artist Tesher's mashup video, 'Young Shahrukh'. Ratnam's use of fantasy-like scenes places the film and its songs in an earlier pre-2000 genre of the song sequence. Song picturizations in pre-2000 Hindi cinema, usually filmed after the song was recorded, were called 'situations' and song composition often took place around them (Morcom 31). Film songs and their picturizations functioned as the forerunners of 'non-resident' media, a term used to designate media not intended for the audience consuming it (Athique 111). In looking at the film's transnational movement, I attend to its songs' imagistic qualities and interpret 'Satrangi Re' (The Colorful One), one of the most remarked upon songs in the film, as a translation of narrative, rather than an escape from it. The film's intradiegetic movement during its transition from narrative to dream- like song sequences and its transnational circulation are marked by a resemblance between interiority and exteriority. In its transnational movement, the link between song and narrative weakens, but at the same time, brings forth new forms of visuality. Such visual presence, already at work in song sequences within their original narratives in pre-2000 Hindi cinema, is the first and preliminary movement of song picturization's transnational circulation.